Comparative plastome assembly of the yellow ironweed (Verbesina alternifolia) using Nanopore and Illumina reads - Tomasello, Salvatore; Manzo, Eleonora; Karbstein, Kevin (Frontiers in Plant Science, 2024)
Chloroplast genomes (plastomes) represent a very important source of valuable information for phylogenetic and biogeographic reconstructions. The use of short reads (as those produced from Illumina sequencing), along with de novo read assembly, has been considered the “gold standard” for plastome reconstruction. However, short reads often cannot reconstruct long repetitive regions in chloroplast genomes. Long Nanopore (ONT) reads can help bridging long repetitive regions but are by far more error-prone than those produced by Illumina sequencing. Verbesina is the largest genus of tribe Heliantheae (Asteraceae) and includes species of economic importance as ornamental or as invasive weeds. However, no complete chloroplast genomes have been published yet for the genus. We utilized Illumina and Nanopore sequencing data and different assembly strategies to reconstruct the plastome of Verbesina alternifolia and evaluated the usefulness of the Nanopore assemblies. The two plastome sequence assemblages, one obtained with the Nanopore sequencing and the other inferred with Illumina reads, were identical, except for missing bases in homonucleotide regions. The best-assembled plastome of V. alternifolia was 152,050 bp in length and contained 80, 29, and four unique protein-coding genes, tRNAs, and rRNAs, respectively. When used as reference for mapping Illumina reads, all plastomes performed similarly. In a phylogenetic analysis including 28 other plastomes from closely related taxa (from the Heliantheae alliance), the two Verbesina chloroplast genomes grouped together and were nested among the other members of the tribe Heliantheae s.str. Our study highlights the usefulness of the Nanopore technology for assembling rapidly and cost-effectively chloroplast genomes, especially in taxonomic groups with paucity of publicly available plastomes.